THE IMPLEMENTATION OF ELECTRONIC-BASED SYSTEM IN REDUCTION OF MEDICATION ERROR: A LITERATURE REVIEW - Saho, Musa; Rr. Tutik Sri Hariyati; Hening Pujasari (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Medication errors have been a persistent issue in healthcare, often overshadowing nurses' ability to focus on patient care. Traditionally, nurses have devoted considerable time to calculating medications—dosages, routes, and frequencies—at the expense of other caregiving duties. This literature review explores the adoption of electronic-based systems to reduce medication errors and associated risks in healthcare settings. The research involved examining databases such as Clinical-key-nursing, Science Direct, ProQuest, Embase, and academic articles, using keywords like